Analisis Ketersediaan dan Kebutuhan Air Irigasi pada Area Lahan Persawahan: Studi Kasus di Desa Karangbale Kabupaten Brebes - Nurokhman, Nurokhman; Feriska, Yulia; Diantoro, Wahudin (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the availability and need of irrigation water in rice fields in Karangbale Village, Brebes Regency. The availability of irrigation water is vital for the sustainability of agriculture, especially rice crops, which are the main commodities in Indonesia. Using quantitative methods, data was collected through field observations, interviews with farmers, and analysis of related documents. The research period lasted from January to June 2025. The results showed that the total effective rainfall during the planting period reached 858.2 mm, which resulted in water availability of 2,136,138 m³ for a land area of 249 Ha. Meanwhile, the total water requirement for rice plants during one planting cycle (120 days) is 600 mm, with the maximum requirement in the vegetative phase of 6 mm/day and the generative phase of 4 mm/day. Analysis of the water balance shows that there is a gap between water availability and demand, where the inflow and outflow from irrigation canals are recorded equally, which is 6,545 m³/s. However, the water requirement for rice plants can reach 1,494,000 m³, indicating that the availability of water does not always meet the water needs of plants, especially in the dry season. Factors affecting the availability of irrigation water in Karangbale Village have been identified, including: garbage accumulation in irrigation canals, sediment accumulation, soil quality, and rainfall variability. Garbage buildup can lead to blockage of water flow and pollution of water quality, while sediment reduces channel capacity and slows flow. Good soil quality can be beneficial for rice plants and other crops. Uneven rainfall fluctuations also have an impact on water availability, creating periods of drought or excess water. Based on these findings, it is recommended that water resource management in Karangbale Village be improved through the following steps: public education on the importance of waste management, repair and maintenance of irrigation infrastructure to reduce sediment accumulation, and training farmers on good soil management practices. These measures are expected to support food security and agricultural sustainability in the region.